Family Interpersonal Communication in Jumbo’s TikTok Ad - Ferdiana Ferdiana; Iksander Iksander (Prodi Ilmu Komunikasi UTM, 2026)
The rapid growth of social media has transformed family communication from a private relational practice into a symbolic representation within digital promotional content. This study examined how family interpersonal communication was represented and interpreted in the TikTok advertisement of the Indonesian animated film Jumbo. Using a descriptive qualitative design and Charles Sanders Peirce’s semiotic approach, this research analyzed visual, audio, and textual signs to identify the relationship between representamen, object, and interpretant. The findings revealed three dominant representational patterns: (1) the nuclear family as a space of emotional validation and affective support; (2) the chosen family as a form of non-biological solidarity; and (3) the intergenerational family as a foundation of identity and moral legitimacy. The advertisement constructed family not merely as verbal interaction but as a multimodal affective and ideological meaning system integrated into an emotional branding strategy. Through empathy, protection, solidarity, and nostalgia, family relationships were positioned as symbolic resources that generated audience engagement and strengthened brand identity. The study contributed to interpersonal communication scholarship by repositioning family interaction as a multimodal symbolic construct within digital media environments.